Knowledge and Utilization of Sexual and Reproductive Health Services Among Secondary Level Students of Bhaktapur, Nepal - Munikar, Sabika; Luitel, Iswari; KC, Rashi (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: According to WHO and ICPD, sexual and reproductive health is defined as “a state of physical, emotional, mental and social well-being in relation to sexuality and reproductive system”. The study aims to assess the knowledge and utilization of sexual and reproductive health services among secondary level students. Methods: Descriptive cross-sectional study was done among 118 adolescent students from selected school by using non probability purposive sampling technique. Self-administered semi-structured questionnaire was used for data collection. Analysis was done in SPSS version 16 using descriptive and inferential statistics. Results: 81.4% participants had adequate knowledge related to SRH services and 25.4% had utilized SRH services. Utilization was found to be associated with gender (p = 0.000), fathers’ education (p = 0.028), mothers’ occupation (p = 0.001), interaction with family (p = 0.040), availability of services within 30 minutes of walking distance (p = 0.000), sexually active in past 12 months (p = .000). Conclusions: Majority of the respondents had adequate knowledge. Utilization among students was found to be low.